2022
DOI: 10.11594/ijmaber.03.09.04
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management Practices and Job Satisfaction: Basis for Development of a Teacher Retention Framework

Abstract: The objective of this research paper is to examine the association between Human Resource Management (HRM) practices and teachers' Job Satisfaction (JS) of private academic institutions in Olongapo City, Philippines. The investigators used a descriptive-correlation research design among 170 conveniently chosen respondents. The study used an adopted and modified research instrument wherein the gathered data underwent descriptive and inferential analysis. The study revealed that private academic institutions pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
0
0
0
1
Order By: Relevance
“…This confirms that a paternal leader can influence his traits (Nishii and Leroy 2022) with other factors that are important for employee retention in the organization. Our second hypothesis is also positive because it confirms that virtual human resources (Mondejar and Asio 2022) during the pandemic was an additional mechanism that links the compassionate trait of a paternal (Gilbert 2021) leader and work engagement activities (Christian et al 2011). We then examined H3, which is rejected because normally, a paternal leader considers himself to be more experienced and has a greater right to decide business decisions, which can have a negative impact on the employees.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This confirms that a paternal leader can influence his traits (Nishii and Leroy 2022) with other factors that are important for employee retention in the organization. Our second hypothesis is also positive because it confirms that virtual human resources (Mondejar and Asio 2022) during the pandemic was an additional mechanism that links the compassionate trait of a paternal (Gilbert 2021) leader and work engagement activities (Christian et al 2011). We then examined H3, which is rejected because normally, a paternal leader considers himself to be more experienced and has a greater right to decide business decisions, which can have a negative impact on the employees.…”
Section: Discussionmentioning
confidence: 88%
“…These programs are intended to have a favorable influence on employee retention and commitment. Organizations have prioritized reducing unneeded and undesirable employee turnover by implementing HR procedures and regulations (Mondejar and Asio 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to the study of Mondejar & Asio, (2022), revealed that private academic institutions practice recruitment and selection processes, evaluate employee performance, provide training and development, appropriate compensation, career planning opportunities, and employee safety, health, and welfare. Furthermore, respondents were satisfied with their supervisors, coworkers, working conditions, compensation and responsibilities; job itself, advancement, security, and recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Administrators' holistic efforts to address teacher retention challenges, such as providing a good working environment, empowering teachers, and caring for their spiritual and professional growth, help them stay in private schools longer (Mondejar & Asio, 2022). Aside from the effort to increase the salary in private schools, administrators can always promote a positive school culture for the teachers (Shrestha, 2022).…”
Section: Implication Of the Studymentioning
confidence: 99%